1981
DOI: 10.1126/science.7233231
|View full text |Cite
|
Sign up to set email alerts
|

Phase Relationships Between Adjacent Simple Cells in the Visual Cortex

Abstract: Adjacent simple cells recorded and "isolated" simultaneously from the same microelectrode placement were usually tuned to the same orientation and spatial frequency. The responses of the members of these "spatial frequency pairs" to drifting sine-wave gratings were cross-correlates. Within the middle range of the spatial frequency selectivity curves, the responses of the paired cells differed in phase by approximately 90 percent. This phase relationship suggests that adjacent simple cells tuned to the same spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(129 citation statements)
references
References 11 publications
8
118
1
1
Order By: Relevance
“…Real and imaginary part are Gabor-like filters that are in quadrature-phase. This statistical result is in line with measurements in V1 [12,11] and related empirical models [13].…”
Section: Simulations With Natural Imagessupporting
confidence: 90%
See 1 more Smart Citation
“…Real and imaginary part are Gabor-like filters that are in quadrature-phase. This statistical result is in line with measurements in V1 [12,11] and related empirical models [13].…”
Section: Simulations With Natural Imagessupporting
confidence: 90%
“…In this example the magnitude and the phase in the Fourier domain of two images were exchanged, and the images which were perceptually more similar to the originals were the ones that carried the phase information. Moreover there is experimental evidence of phase coupled Gabor-like filters in V1 [12,11]. For this reason, Daugman [13] suggested that the receptive field in the first stage could be seen as Gabor sensors defined in the complex domain: the real and the imaginary part are essentially the same Gabor filter but with phases in quadrature.…”
Section: Introductionmentioning
confidence: 99%
“…Yao Jia-Xin pointed out that table tennis event was net separated small ball event that had both interests and competitiveness, it had profound history and widely mass base in China, development of the event up to now, its competitions not only limited in contesting among athletes techniques, tactics, physical quality and styles, but also paid more attentions to athletes' psychological consciousness contesting [4][5][6].…”
Section: Summary Of Table Tennis Benefits On Students' Psychological mentioning
confidence: 99%
“…According to such purpose, log-Gabor filters are chosen for modeling the receptive field of the simple cortical cells as proposed in Daugman (1985); Marcelja (1980);and Field (1987). Simple cells are known to be organized in pairs in quadrature of phase (Pollen and Ronner, 1981), justifying the choice of complex-valued filters. The choice of the bandwidth in orientation is motivated by the simple cell orientation resolution which has been evaluated as around 20-40 degrees of full bandwidth at half response (Hubel, 1988;Daugman, 1985).…”
Section: Bandpass Log-gabor Filtersmentioning
confidence: 99%